STUDY THE CREEP OF TUBULAR SHAPED FIBER REINFORCED COMPOSITES - Najat J. Saleh; Adnan A. Abdul Razak (Tikrit Journal of Engineering Sciences, 2013)
Inpresent work tubular –shaped fiber reinforced composites were manufactured byusing two types of resins ( Epoxy and unsaturated polyester) and separatelyreinforced with glass, carbon and kevlar-49 fibers (filament and woven roving),hybrid reinforcement composites of these fibers were also prepared. The fiberswere wet wound on a mandrel using a purposely designed winding machine,developed by modifying an ordinary lathe, in winding angle of 55° for filament. A creep test was made of either the fulltube or specimens taken from it. Creep was found to increase upon reinforcementin accordance to the rule of mixture and mainly decided by the type of singleor hybridized fibers. The creep behavior, showed that the observed strain tendsto appear much faster at higher temperature as compared with that exhibited atroom temperate. The creep rate also found to be depending on fiber type, matrixtype, and the fiber /matrix bonding. The creep energy calculated fromexperimental observations was found to exhibit highest value for hybridizedreinforcement.